The Influence of Teamwork, Occupational Safety and Health On Employee Performance With Compensation As a Moderating Variable in Crew Catering PT. XYZ At the Java Sea Offshore Platform Facility - Ranthy Pancasasti; Mochamad Alvin Fikri; Yopi Ilham Akbar Putra; Risa Pusvitasari (Journal of Business and Behavioural Entrepreneurship, 2022)
Background: Performance is the quality and quantity of an employee's work in fulfilling of employee primary responsibilities as an employee in accordance with the responsibilities assigned to them. Good performance will produce satisfactory results, but poor performance will produce bad results. This is company concers, how to achieve effective company goals through good performance. Teamwork, occupational safety and health and compensation some of the factors can affect employe performance. Purpose: The purpose of this study was to examine the effect of teamwork, occupational health And safety affected by compensation as a moderating variable on employee performance. Originality / value: The novelty of this study is that no prior research has discussed teamwork, occupational health and safety affected by compensation as a moderating variable on employee performance on the performance of employee in the catering crew at PT.XYZ on the offshore platform of the java sea. Research limitations: The limitation in this study is only to analyse the magnitude of the influence of teamwork, occupational health and safety affected by compensation as a moderating variable on employee performance on the performance of employee in the catering crew at PT.XYZ on the offshore platform of the java sea. Design/methodology/approach: A questionnaire with a 10-point Likert scale as an assistance tool is used in the quantitative research method, and random sampling is used for the sampling methods.The number of samples used to test four (4) hypotheses could have been as many as 90 pieces.Path coefficients are examined for statistical significance using structural equation modeling. Findings: The results showed that teamwork had a positif and significant effect on employee performance, occupational health and safety had a positif and significant effect on employee performance, compensation is positive and significant as a moderator of the relationship between teamwork and employee performance, while compensation is negative and insignificant as a moderator of the relationship between occupational health and safety and employee performance, according to the findings.